The Great Convergence: Information Technology and the New Globalization (excerpts) - Baldwin, Richard; Левченко, Олег (Journal of Economic Sociology, 2017)
The book is devoted to globalization, which has dramatically changed in the 1990s, according to Richard Baldwin, mainly because of transformations in information and communication technology (ICT), resulting in a significant decrease in the costs of moving ideas. This shift indicated a new stage of development of globalization processes and caused a convergence of developed and developing states. This book includes five parts, which discuss the history of globalization, the economics of globalization, the states’ designs of a national policy, and forecasting its future. The Journal of Economic Sociology publishes the introduction to the book, in which the author presents the main idea of his manuscript. He justifies his new perspective on globalization, sequentially describing the processes that accelerate it, including the decreased costs of moving goods, decreased communication costs, and a reduction in moving people. Additionally, the author concludes how the presented changes in globalization affect national economies.